Toward a Corporate Duty for Lead Companies to Respect Human Rights in Their Global Value Chains?. (December 2020) - Bright, Claire; Marx, Axel; Pineau, Nina; Wouters, Jan
Abstract: The corporate responsibility to respect human rights was formally introduced in 2011 with the unanimous endorsement of the UN Guiding Principles on Business and Human Rights (UNGPs) by the UN Human Rights Council. It is grounded in social expectations and forms part of the companies' "social license to operate." This paper argues that this responsibility is progressively turning into a legal duty for lead companies to respect human rights in those types of value chains which are characterized by a high level of control by a lead company over its business partners. Our argument rests on two recent legal developments. Firstly, the article analyzes the judicialization of the corporate responsibility to respect in the case law on parent company liability in various jurisdictions, which, we argue, is highly likely to have some implications in relation to certain types of value chains so as to trigger the liability of lead companies for the human rights harms arising out of the activities of entities over which they exercise sufficient control. Secondly, the article delves into the legislative developments which increasingly require lead companies to exercise due diligence so as to prevent and address adverse human rights impacts in their own activities and global value chains.